Genomic characterisation of an international Pseudomonas aeruginosa reference panel indicates that the two major groups draw upon distinct mobile gene pools. Issue 14 (12th June 2018) - Freschi, Luca; Bertelli, Claire; Jeukens, Julie; Moore, Matthew P; Kukavica-Ibrulj, Irena; Emond-Rheault, Jean-Guillaume; Hamel, Jérémie; Fothergill, Joanne L; Tucker, Nicholas P; McClean, Siobhán; Klockgether, Jens; de Soyza, Anthony; et al.
Abstract: Pseudomonas aeruginosa is an important opportunistic pathogen, especially in the context of infections of cystic fibrosis (CF). In order to facilitate coordinated study of this pathogen, an international reference panel of P. aeruginosa isolates was assembled. Here we report the genome sequencing and analysis of 33 of these isolates and 7 reference genomes to further characterise this panel. Core genome single nucleotide variant phylogeny demonstrated that the panel strains are widely distributed amongst the P. aeruginosa population. Common loss-of-function mutations reported as adaptive during CF (such as in mucA and mexA ) were identified amongst isolates from chronic respiratory infections. From the 40 strains analysed, 37 unique resistomes were predicted, based on the Resistance Gene Identifier method using the Comprehensive Antibiotic Resistance Database. Notably, hierarchical clustering and phylogenetic reconstructions based on the presence/absence of genomic islands (GIs), prophages and other regions of genome plasticity (RGPs) supported the subdivision of P. aeruginosa into two main groups. This is the largest, most diverse analysis of GIs and associated RGPs to date, and the results suggest that, at least at the largest clade grouping level (group 1 vs group 2), each group may be drawing upon distinct mobile gene pools. Abstract : By genome sequencing Pseudomonas aeruginosa from a reference panel, we show that the organism divides into two major groups on the basis of both SNP phylogeny and accessory genome content.